Development and Evaluation of a Therapist Training Program for Psilocybin Therapy for Treatment-Resistant Depression in Clinical Research - Tai, Sara J.; Nielson, Elizabeth M.; Lennard-Jones, Molly; Johanna Ajantaival, Riikka-Liisa; Winzer, Rachel; Richards, William A.; Reinholdt, Frederick; Richards, Brian D.; Gasser, Peter; Malievskaia, Ekaterina (Frontiers in Psychiatry, 2021)
Introduction: Psychological support throughout psilocybin therapy is mandated by regulators as an essential part of ensuring participants’ physical and psychological safety. There is an increased need for specially trained therapists who can provide high-quality care to participants in clinical studies. This paper describes the development and practical implementation of a therapist training program of psychological support within a current phase IIb international, multicenter, randomized controlled study of psilocybin therapy for people experiencing treatment-resistant depression. Description of Training Program: This new and manualized approach, based on current evidence-based psychotherapeutic approaches, was developed in partnership with different mental health researchers, practitioners, and experts; and has been approved by the FDA. Training consists of four components: an online learning platform; in-person training; applied clinical training; and ongoing individual mentoring and participation in webinars.This paper provides a brief overview of the method of support, the rationale and methodology of the training program, and describes each stage of training. The design and implementation of fidelity procedures are also outlined. Lessons learned: As part of the phase IIb study of psilocybin therapy for treatment-resistant depression, 65 health care professionals have been fully trained as therapists and assisting therapists, across the US, Canada and Europe. Therapists provided informal feedback on the training program. Feedback indicates that the didactic and experiential interactive learning, delivered through a combination of online and in-person teaching, helped therapists build conceptual understanding and skill development in the therapeutic approach. Clinical training and engagement in participant care, under the guidance of experienced therapists, were considered the most beneficial and challenging aspects of the training. Conclusions: Clinical training for therapists is essential for ensuring consistently high-quality psilocybin therapy. Development of a rigorous, effective and scalable training methodology has been possible through a process of early, active and ongoing collaborations between mental health experts. To maximize impact and meet phase III and post-approval need, enhanced online learning and establishing pathways for clinical training are identified as critical points for quality assurance. This will require close public, academic and industry collaboration.